1999
DOI: 10.1590/s0066-782x1999000300004
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous origin of the left coronary artery from the pulmonary trunk. Clinical features and midterm results after surgical treatment

Abstract: AOLCA is a rare disease. Most patients show early signs of severe HF associated with ECG findings. Surgical therapy must be instituted early in the disease, preferentially through aortic implantation of the anomalous coronary artery, with a high possibility of success. Shortly after surgery, clinical and ECG improvement, as well as normalization of left ventricular function, should be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The electrocardiogram is of key importance in the diagnosis of anomalous origin of the left coronary artery, where the presence of a Q wave in the D1 and aVL leads suggests the diagnostic hypothesis of this heart disease. Amaral et al 13 found a Q wave in aVL in 91% of the patients; Bunton et al 5 in 95% of the cases; and Isomatsu et al 14 in 82%. In the present study, this rate was 83% of the patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The electrocardiogram is of key importance in the diagnosis of anomalous origin of the left coronary artery, where the presence of a Q wave in the D1 and aVL leads suggests the diagnostic hypothesis of this heart disease. Amaral et al 13 found a Q wave in aVL in 91% of the patients; Bunton et al 5 in 95% of the cases; and Isomatsu et al 14 in 82%. In the present study, this rate was 83% of the patients.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, three patients developed supravalvar stenosis, and two required surgical reintervention. This is the most frequent complication, and its incidence ranges from 18 to 60% 3,4,5,10,13 . The need for surgical reintervention is of approximately 12% to 42%.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended in all patients at the time of diagnosis, regardless of age or symptoms [13]. Studies known from literature show immediate clinical improvement after surgery and normalization of left ventricle function should be expected [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Without the correct diagnosis and corrective surgical treatment there is a reported 90% mortality rate during infancy for ALCAPA [3]. The reported prognosis in the literature for infants with ALCAPA following surgery is a 5-year survival rate of 91% [2].…”
Section: Discussionmentioning
confidence: 99%